PRINSIP-PRINSIP EKONOMI ISLAM: SEBUAH KAJIAN AWAL - Junaidi, Heri; Zainuddin, Cholidi (Program Studi Muamalah Fakultas Syariah dan Hukum, 2017)
Up to the present time, economics can't succeed in building economic justice and property for all mankind. In reality, there is an economic imbalance among the poor and the rich nations. In order to better the situation, the economics changed paradigm and vision. Moslem scientists tried to find an alternative system which could be relevant to the principles of Islamic Law. The alternative system is economy of Islam. Economic of Islam is established based on four philosophical bases namely, unity of God, justice and balances, freedom and human's responsibility. In the economics of Islam, product and services of banking have some specific rules such as abolishing interest, the expanse is used to finance legal efforts basing on principles of Islamic law and eliminate unproductive speculation.